2018
DOI: 10.12680/balneo.2018.174
|View full text |Cite
|
Sign up to set email alerts
|

The importance of physical exercise-bone mass density correlation in reducing the risk of vertebral and non-vertebral fracture in patients with osteoporosis

Abstract: Introduction. Osteoporosis is a systemic health condition, predominantly in the skeleton, characterized by the decreasing bone strength and bone density as well as by the modification of this structure, being prone to an increased fracture risk. The bone strength of the bone depends on the density and quality of the bone. The bone density was measured by DEXA imagery investigation which uses the dual absorptiometry by X-rays.Material and method. The study was conducted over a period of one year on a total of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A review of 62 studies from 4 databases has evaluated the quality of life through several questionnaires. Thus, it was found that obesity, the decrease of the physical activity (7) and the female sex were the factors that decreased the quality of life. Additionally, the patients' educational level, the psychological stress, the depression, the social and inter-family relations (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…A review of 62 studies from 4 databases has evaluated the quality of life through several questionnaires. Thus, it was found that obesity, the decrease of the physical activity (7) and the female sex were the factors that decreased the quality of life. Additionally, the patients' educational level, the psychological stress, the depression, the social and inter-family relations (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis is one reason why the distal radius fractures occur, that is why the early diagnosis of this health condition enables the prevention of the fracture by evaluating the fracture risk and it also enables to establish the appropriate therapeutic strategy (19). It is very important the calcium intake from food and medication (20,21) but also the D vitamin that has its role in the bone metabolism, which reduces the risk to have a fracture (22) . As for the fractures of the children, it is important to mention the role of calcium, of magnesium and of D vitamin in the recovery after the fracture and in the presence of the vasomotor tonus.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of the sequelae after the fracture is complex and involves: [1] the antalgic and antiinflammatory medication to reduce the algic /inflammatory symptomatology, [2] the electric therapy (29) has different roles: antialgic/ antiinflammatory, vasodilating, myorelaxing/ relaxing • the currents of low frequence: TENS, with electrodes applied on the painful spot, the frequence 50-100 Hz, the intensity 10-40mA, the duration of 10 minutes • The ultrasounds in pulsatile application, with a frequence of 1 MHz, the intensity of 0.4-0.6W/cm² by using the antiinflammatory gel (30,31). The application of ultrasound is useful in the pathology of the soft tissues but also in the joint one whereas the mechanical and thermal effects are deeply felt and provide with the blood flow necessary to the recovery process (21,32). The ultrasound have their role in reducing the pain, the joint stiffness and the muscular contraction.…”
Section: Introductionmentioning
confidence: 99%